Kontribusi Adverse Childhood Experiences Terhadap Self-Criticism Pada Emerging Adulthood Di Kota Padang - Aura Ansri; Mario Pratama; Iftita Rahmi; Wirza Feny Rahayu (Psychopolytan : Jurnal Psikologi, 2026)
This study aimed to ex amine the contribution of ACEs to self-criticism among emerging adults in Padang City. A quantitative correlational design was employed with 101 emerging adults aged 18–25 years who had experienced at least one form of ACE, selected using purposive sampling. Data were collected online using the Forms of Self-Criticizing/Attacking and Self-Reassuring Scale (FSCRS) and the World Health Organization Adverse Childhood Experiences International Questionnaire (WHO ACE-IQ). Multiple linear regression analysis. The findings indicated that ACEs significantly contributed to self-criticism. Partially, the dimensions of childhood maltreatment and family/household dysfunction showed significant contributions, whereas violence outside the home did not demonstrate a significant effect. These results suggest that adverse experiences occurring within the family environment play a critical role in shaping self-critical tendencies during emerging adulthood. This study highlights the importance of early prevention and psychological interventions targeting individuals with a history of childhood adversity.